Automated segmentation of biventricular contours in tissue phase mapping using deep learning. (2nd September 2021) - Shen, Daming; Pathrose, Ashitha; Sarnari, Roberto; Blake, Allison; Berhane, Haben; Baraboo, Justin J.; Carr, James C.; Markl, Michael; Kim, Daniel
Abstract : Tissue phase mapping (TPM) is an MRI technique for quantification of regional biventricular myocardial velocities. Despite its potential, clinical use is limited due to the requisite labor‐intensive manual segmentation of cardiac contours for all time frames. The purpose of this study was to develop a deep learning (DL) network for automated segmentation of TPM images, without significant loss in segmentation and myocardial velocity quantification accuracy compared with manual segmentation. We implemented a multi‐channel 3D (three dimensional; 2D + time) dense U‐Net that trained on magnitude and phase images and combined cross‐entropy, Dice, and Hausdorff distance loss terms to improve the segmentation accuracy and suppress unnatural boundaries. The dense U‐Net was trained and tested with 150 multi‐slice, multi‐phase TPM scans (114 scans for training, 36 for testing) from 99 heart transplant patients (44 females, 1‐4 scans/patient), where the magnitude and velocity‐encoded ( V x, V y, V z ) images were used as input and the corresponding manual segmentation masks were used as reference. The accuracy of DL segmentation was evaluated using quantitative metrics (Dice scores, Hausdorff distance) and linear regression and Bland‐Altman analyses on the resulting peak radial and longitudinal velocities ( V r and V z ). The mean segmentation time was about 2 h per patient for manual and 1.9 ± 0.3 s for DL. Our network produced good accuracy (median Dice = 0.85 for left ventricle (LV), 0.64 for right ventricle (RV), Hausdorff distance = 3.17 pixels) compared with manual segmentation. Peak V r and V z measured from manual and DL segmentations were strongly correlated ( R ≥ 0.88) and in good agreement with manual analysis (mean difference and limits of agreement for V z and V r were −0.05 ± 0.98 cm/s and −0.06 ± 1.18 cm/s for LV, and −0.21 ± 2.33 cm/s and 0.46 ± 4.00 cm/s for RV, respectively). The proposed multi‐channel 3D dense U‐Net was capable of reducing the segmentation time by 3, 600‐fold, without significant loss in accuracy in tissue velocity measurements. Abstract : This study describes an automated image segmentation method for biventricular tissue phase mapping (TPM) images with deep learning. We implemented a multi‐channel 3D dense U‐Net that trained on magnitude and phase images, which is significantly faster than manual contouring, without significant loss in segmentation accuracy or TPM parameters.